Virtual teams for NPD – an innovative experience for R&D engineers - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2009)
New interaction tools such as internet allow companies to gain valuable input from research and development (R&D) engineers via virtual teams. Consequently, engineers also get more expertise in diminutive time frames. Virtual R&D teams present the key impetus to the technology acquisition process. The present knowledge-economy era is characterized by short product life-cycles. Virtual R&D teams may reduce time-to-market, make available a large pool of new product know-how and provide greater flexibilities, which are the key success factors in a competitive market. This comprehensive review contains almost 100 references and covers the recent literature with emphasis on the topic. The review has focused on authentic and reputed publications and extracts the results. This article presents the type of virtual teams and their main features and explains how virtual R&D team can play a prominent role in developing new products. The article is evolved future study guideline and also illustrates how to apply virtual interaction tools and integrate engineers into the innovation process. Management of virtual R&D teams in new product development (NPD) processes in an innovative, effective and efficient is of a high importance, but the issue has been poorly addressed in the previous studies. Findings show that virtual R&D team provides valuable input for new product development and R&D engineers are able to attain virtual experience.